2013
DOI: 10.4103/2141-9248.117934
|View full text |Cite
|
Sign up to set email alerts
|

Large vesico-vaginal fistula caused by a foreign body

Abstract: Foreign body is a rare cause of vesico-vaginal fistula most often reported in developed countries. In developing countries obstructed labor is the commonest cause of fistula. A nulliparous 19-year-old female presented with a 3-week history of a foreign body in the vagina causing urinary incontinence and offensive vaginal discharge. Her guardian allegedly inserted the foreign body after she refused a pre-arranged marriage. A plastic container was removed from the vagina under general anesthesia. A large vesico-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In the literature, no report currently exists regarding fistula formation after battery vaginal insertion, but it is biologically plausible to have similar complications in the vagina. 11 …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, no report currently exists regarding fistula formation after battery vaginal insertion, but it is biologically plausible to have similar complications in the vagina. 11 …”
Section: Discussionmentioning
confidence: 99%
“…While vesicovaginal fistulas occasionally can occur secondary to underlying malignancies, they rarely take place secondary to vaginally inserted FBs [9]. Nonetheless, several cases of vesicovaginal fistulas have been reported in literature among adults (more than 18 years old) [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Vesico-vaginal fistulas are treated with both delayed transvaginal (11/29) and transabdominal (10/29) approaches. Where available, success rates seem to be high: in the 6 unsuccessful cases reported in the literature, all patients were successfully retreated (table 1) [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. Pushkar et al [2], moreover, showed a success rate of UVF treatment of 90 and 98% at primary and secondary treatment, respectively; 52% of the patients developed stress urinary incontinence, which was successfully treated with sling procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies may be inserted during sexual intercourse or masturbation [5], with contraceptive purposes [6], as neglected pessaries [7] or, rarely, during rape or as punishment [8]. …”
Section: Introductionmentioning
confidence: 99%